ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN LINIER DUA VARIABEL DI SMP AL-MAHMUD PLUS-CILILIN - Regina Octa Dwi Ningrum; Eva Dwi Minarti (IKIP Siliwangi, 2022)
Mathematics education is a very influential role for us because we will encounter it in aspects of evryday life. This study aims to observe and examine the difficulties of private junior hight school students in mathematics lessons, namely the SPLDV (Two-variable linier equation system) material in online learning for the 2020 and 2021 academic years. This research was carried out by one of the private junior high schools in the Cililin area. The subjects of this study werre 27 students and from class VIII. This study has test questions white indicators that have been applied as an instrument using newmen steps. In this study, using a descriptive quealitative approach, the findings obtained using the steps of te newmen procedure, some student experienced errors white indicator for solving problems involving SPLDV (a system of two-variable linier equations). The results of the analysis show that reading errors (reading errors) reading examples of math problems, so that student are femiliarwhite symbols commonly used in math problems, comprehension errors (comprehension errors) students are given learning and practice working on more complexn questions. Intensive, and learning materials are more related to the surrounding environment and daily life so that students easily find things that are know and things that are asked in questions, transformation errors write down students’ method in process skills. This is done by increasing that number of practice questions white a variety of varied questions so that students’ skills and accuracy in analyzing and finding methods and procedures for arithmatic operations increase, process skill errors (processs kill errors) mastery of student formulas, students should be emphasized more for memorize it but to be understood. Teachers should provide the concept of mathematical formulas so that students are familiar white the steps of the problem solving process and are not fixated one the formulas they memorized, and writing errors in the final answere (encode errors). Errors in doing math problems and students who have low cognitive abilities.